Phytochrome A and B Regulate Primary Metabolism in Arabidopsis Leaves in Response to Light - Han, Xiaozhen; Tohge, Takayuki; Lalor, Pierce; Dockery, Peter; Devaney, Nicholas; Esteves-Ferreira, Alberto A.; Fernie, Alisdair R.; Sulpice, Ronan (Frontiers in Plant Science, 2017)
Primary metabolism is closely linked to plant productivity and quality. Thus, a better understanding of the regulation of primary metabolism by photoreceptors has profound implications for agricultural practices and management. This study aims at identifying the role of light signaling in the regulation of primary metabolism, with an emphasis on starch. We first screened seven cryptochromes and phytochromes mutants for starch phenotype. The phyAB mutant showed impairment in starch accumulation while its biomass, chlorophyll fluorescence parameters, and leaf anatomy were unaffected, this deficiency being present over the whole vegetative growth period. Mutation of plastidial nucleoside diphosphate kinase-2 (NDPK2), acting downstream of phytochromes, also caused a deficit in starch accumulation. Besides, the glucose-1-phosphate adenylyltransferase small subunit (APS1) was down-regulated in phyAB. Those results suggest that PHYAB affect starch accumulation through NDPK2 and APS1. Then, we determined changes in starch and primary metabolites in single phyA, single phyB, double phyAB grown in light conditions differing in light intensity and/or light spectral content. PHYA is involved in starch accumulation in all the examined light conditions, whereas PHYB only exhibits a role under low light intensity (44 ± 1 μmol m-2 s-1) or low R:FR (11.8 ± 0.6). PCA analysis of the metabolic profiles in the mutants and wild type (WT) suggested that PHYB acts as a major regulator of the leaf metabolic status in response to light intensity. Overall, we propose that PHYA and PHYB signaling play essential roles in the control of primary metabolism in Arabidopsis leaves in response to light.